Pengaruh kenaikan suku bunga THE FED dan Inflasi terhadap Harga Saham pada perusahaan Perbankan dengan nilai tukar Rupiah sebagaiVariabel Intervening - Raqil Alfahing; Elfiswandi .; Rindy Citra Dewi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of capital structure and dividend policy on firm value with financial performance as an intervening variable in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The population of this study consists of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the 2020–2024 period, with the sample selected using the purposive sampling method. The data analysis methods employed in this study are multiple linear regression analysis and path analysis. The results of this study indicate that capital structure partially has a significant effect on financial performance. Dividend policy partially has a significant effect on financial performance. Capital structure and dividend policy simultaneously affect financial performance. Furthermore, financial performance partially does not have a significant effect on firm value. Capital structure partially does not have a significant effect on firm value, while dividend policy partially has a significant effect on firm value. Capital structure, dividend policy, and financial performance simultaneously affect firm value. The results of the intervening variable test show that financial performance is not able to mediate the effect of capital structure on firm value, and is also not able to mediate the effect of dividend policy on firm value in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange during the 2020–2024 period.